Pengolahan Sampah Rumah Tangga Menjadi Eco Enzim Yang Dapat Dimanfaatkan Masyarakat Desa Arul Putih - Nikmah, Askura; Kurniawan, Dimas; Putri, Adrinisyah; Sahdi, Jurida (Universitas Gajah Putih, Indonesia, 2023)
Garbage is one of the problems faced by many cities around the world. Indonesia is one of the largest developing countries contributing to waste in the world. Indonesia is the second largest contributor of waste with a volume of 187.2 million tons / year, with China in first position with 262.9 million tons / year. In 2003, a doctor from Thailand named Dr. Rosukon Poompanvong received an award from FAO for the discovery of eco enzymes. This program is an enabler in the community of Alur Putih village in order to be able to utilize unused organic kitchen waste to be beneficial for the environment. This activity will be carried out on Thursday, October 19, 2023. Before starting the activity, the group KKNT went through several stages discussions about activity partners, learning material about eco enzyme in the Alur Putih village community, then after that we could empower the targets that had been set through through the results of group discussions.